2020
DOI: 10.1155/2020/4086320
|View full text |Cite
|
Sign up to set email alerts
|

Irregularity Effects of Masonry Infills on Nonlinear Seismic Behaviour of RC Buildings

Abstract: Despite extensive research studies, the seismic response of infilled reinforced concrete buildings remains an open problem due to both the complexity of the interaction between the infill and the frame and the large number of parameters involved. Thus, guidelines for both modelling and analysis are still lacking and the infill walls are normally treated as nonstructural components in seismic codes. However, it may be not conservative to neglect the influence of infills. In fact, the infill masonry walls may si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Nevertheless, numerous studies demonstrated that the irregular arrangement of infill walls in RC frames can cause serious damage to structures under earthquake excitation (Ferraioli and Lavino, 2020;Hermanns et al, 2014). Thus, this paper suggests that the shear micro-springs representing the nonlinear behavior of infill walls can be embedded into the MRLEs of the frame structures, and also use the pinching model to simulate their hysteretic behavior.…”
Section: Discussionmentioning
confidence: 95%
“…Nevertheless, numerous studies demonstrated that the irregular arrangement of infill walls in RC frames can cause serious damage to structures under earthquake excitation (Ferraioli and Lavino, 2020;Hermanns et al, 2014). Thus, this paper suggests that the shear micro-springs representing the nonlinear behavior of infill walls can be embedded into the MRLEs of the frame structures, and also use the pinching model to simulate their hysteretic behavior.…”
Section: Discussionmentioning
confidence: 95%
“…Seismic analysis procedures are categorized into linear and nonlinear methods, each further divided into static and dynamic procedures. The linear static technique is widely used due to its simplicity [10,11], while linear dynamic techniques offer diverse approaches for studying time-varying structural reactions during seismic events [12,13]. Figure 1 illustrates the combination of these seismic analysis procedures.…”
Section: Introductionmentioning
confidence: 99%
“…It also represents in our country the majority of the urban heritage, especially in the north and in the highlands, which is generally known as areas very vulnerable to earthquakes. Here, we are concerned with the observation and study between these walls linked to frames without gap and the masonry walls, which is called "chained masonry walls" that is a special case of infill masonry [1,2].…”
Section: Introductionmentioning
confidence: 99%